Praktik Pembuatan Pupuk Kandang dan Pemanfaatan Lahan Kosong Sebagai Lahan Produksi Hijauan Makanan Kambing - Bagus Haryono; Angela Ayu Putri; Anugrah Akbar; Celine Sola Gracia Lumban Gaol; Gibran Aulia Muhammad; Hasna Maulida Zahra; M. Irfan; Nurlela Dwi Anggraini; Ragil Meiliana Nur Fitri; Rizky Setiawan; Yunita Puspitarini (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
KKN UNS, located in Kapungan Village, Polanharjo District, Klaten Regency, organized a work program entitled 'Practice of making slurry from goat manure and utilizing vacant land for goat feed production'. The purpose of this program is to increase the knowledge and skills of goat managers in Kapungan Village about the conversion of goat droppings into fertilizer and the management of uncultivated land for plantation to improve the care of goats as feed production for goats. to increase understanding. This activity takes place in Kapungan Village, Polanharjo District, Klaten Regency, Central Java. Methods of activity include lectures, discussions, and demonstrations. The results of the practice of making fertilizer from goat dung in Kapungan village and using uncultivated land as a production area for goat feed were based on the reactions of the participants who showed a high level of interest in the training materials as persons involved in livestock and agriculture. About training goals and methods. Through the training activities, the participants became more aware of the importance of feeding livestock according to their nutritional level. For the residents of Kapungan village, the direct impact of the practice of producing compost from goat dung and using uncultivated land as a goat feed production area is the development of suitable huts to reduce goat mortality. Knowledge of management and effective feeding of goats. Kapungan Village has a very high rate of goat rearing. In addition, the community gained knowledge about land management practices for animal feed and goat dung disposal